Factors influencing kombucha production: effects of tea composition, sugar, and SCOBY - DARTORA, Bruna; SANT’ANNA, Voltaire; HICKERT, Lilian Raquel; FENSTERSEIFER, Mariana; AYUB, Marco Antônio Zachia; FLÔRES, Simone Hickmann; PEREZ, Karla Joseane (Food Science and Technology, 2023)
Kombucha is a functional beverage that lacks studies toward standardization of process parameters; thus, the present work aims to evaluate the effect of sucrose content, initial SCOBY mass, and tea composition on several characteristics of the final beverage. For this purpose, a factorial design was performed, and the effect of the three variables was statistically evaluated. All kombuchas were within Brazilian regulation standards (higher than 2.5 and lower than 130 mgEq/L) and can be classified as non-alcoholic beverages. Kombucha yield ranged from 87.3% to 96.4%; SCOBY growth, from 41.11 to 62.08%; turbidity, from 108 to 421.5 NTU; acetic acid, from 3.78 to 5.33 mg/mL; glycerol, from 0.25 to 0.52 mg/mL; and ethanol content, from 1.90 to 3.21 mg/mL. Results showed that kombucha yield, pH, and SCOBY growth were significantly influenced by the SCOBY mass; acidity was greatly affected by the tea composition; kombucha’s turbidity was significantly affected by the sucrose content and the interaction of the sugar content and tea composition; and glycerol, alcohol, and acetic acid were not affected by the parameters evaluated. Results bring science-based information about this global trending beverage, seeking high quality and standardization.